Genetic structure, phylogeography, and demography of Anadara tuberculosa (Bivalvia) from East Pacific as revealed by mtDNA: Implications to conservation - Diringer B. (2019)
Results presented in this research were partially funded by the NGO Hivos (Ecuador), the Subsecretaría de Acuacultura—MAGAP (Contract number N°SA-010 -2014) and Concepto Azul (Ecuador) and the Programa de Ciencia y Tecnología de la Presidencia del Consejo de Ministros—FINCyT through an assignment (Contract number N°71-FINCYT-PITEI-2010) along with private funds from MEDA, Marinazul, Inversiones Silma, and Incabiotec (Peru). B.D. was supported by a schol‐arship from the Franco Peruvian School of Life Sciences and K.P. by FONDECYT (CONVENIO DE GESTIÓN N° 015-2013). We are grate‐ful to CIENCIACTIVA-CONCYTEC for its support through a Molecular Biotechnology Master Program scholarship to K.P. We thank Saverio Vicario for his valuable criticism on an early version of this paper. The authors take the opportunity to express their respect to each of the concheros and concheras of Colombia, Ecuador, and Peru, in recogni‐tion of the hard work they do to support their families, as well as efforts to continue improving the activity, protecting the resource and the mangrove ecosystem for future generations. We thank Rita Castilho and an anonymous reviewer for their constructive criticism.